Polyana is the First Sports Park Built in Irkutsk - Kozak, Alisa (project baikal, 2015)
Irkutsk breaks the stereotypes: a park for unusual and traditional sports was opened on the left bank of the Angara. Soon there will be an open complex with a tennis court, a climbing wall, a rope track together with diverse infrastructure. The first sport park in Siberia will become a year-round recreation area.
Keywords: sports; outdoor activities; park; urban environment; private-public partnership; public space